Android Needs Analysis as A Mobile Learning Media in Special School - Maulana, Ghivari Reza; Widyastono, Herry; Rahman, Abdul (Proceeding of International Conference on Special Education in South East Asia Region, 2022)
The study aims to collect data to measure the benefits and constraints of using Android smartphones as mobile learning in special education institutions and why they are needed. This study uses a descriptive quantitative method using a questionnaire distributed through google forms filled out by 62 teachers of special or inclusive schools in Indonesia. The data analysis method was carried out using SPSS 25 with the following instrument scale and category by Azwar (2014). The results of this study are that teachers experience high benefits of 62.9%, experience several obstacles, and show the highest score at moderate with 82.3% percent. The teacher also feels that using Android as a learning media is easy because various platforms are provided. However, apart from the benefits, teachers also experience several obstacles in their use, such as the lack of socialization or training, and concern about the negative impact on students with special needs.